Two new species of Sciadicleithrum (Monogenea: Dactylogyridae), gill parasites of Geophagus proximus (Castelnau) (Teleostei: Cichlidae), from the upper Paraná River floodplain, Brazil - Bellay, Sybelle; Takemoto, Ricardo Massato; Yamada, Fábio Hideki; Pavanell, Gilberto Cezar (Zootaxa, 2009)
Sciadicleithrum kritskyi n. sp. and Sciadicleithrum paranaensis n. sp. are described from the gills of the acará tinga, Geophagus proximus (Cichlidae), from the upper Paraná River floodplain, Brazil. The most distinctive feature of Sciadicleithrum kritskyi n. sp. that distinguishes it from other members of Sciadicleithrum is the presence of the dorsal bar with a delicate anteromedial projection. Sciadicleithrum paranaensis n. sp. differs from other congeners by having the accessory piece composed of a variable sheath with a ring in the medial portion enclosing the distal shaft of the male copulatory organ. Sciadicleithrum paranaensis n. sp. can be differentiated easily from S. kritskyi n. sp. by having a vaginal aperture on the ventral body surface, and anchors that are similar in size.